Energy Audit to Optimize Electrical Energy Consumption at Siti Khodijah Sepanjang Hospital Sidoarjo using The Analytical Hierarchy Process Method - Mochamad Hadi Saputra; Muhamad Haddin; Arief Marwanto (Lembaga Pengembangan Kinerja Dosen, 2025)
Siti Khodijah Hospital, type B hospital, is one of Muhammadiyah's health charities which is located in 260 Pahlawan Road, Sepanjang, Sidoarjo, East Java. The majority of the operating activities in this hospital use electrical energy, such as the use of medical equipment and other medical equipment that requires the consumption of electrical energy with a large enough capacity. The use of the AHP (Analytical Hierarchy Process) method has the aim of obtaining optimal results in making a decision, namely by simplifying a complex problem that is not structured and systematic. The results of this energy audit are able to provide new ideas to the hospital head through savings programs designed based on the 4M+1E concept (Man, Machine, Method, Material and Environment). The implementation of the results of this study can reduce the cost of using electrical energy by 14%, which is IDR 375,800,000 of the year's electricity costs.